RNA 시퀀싱과 QTL 분석을 통한 콩 내습성 관련 후보유전자 탐색 - 산지브쿠마르둥가나(Sanjeev Kumar Dhungana); 서정현(Jeong-Hyun Seo); 박지희(Ji-Hee Park); 성정숙(Jung-Sook Sung); 김홍식(Hong-Sik Kim); 강범규(Beom-Kyu Kang); 신상욱(Sang-Ouk Shin); 백인열(In-Youl Baek); 정찬식(Chan-Sik Jung) (Korean journal of breeding, 2021)
Flooding stress causes a significant reduction in soybean yield. The development of flood-tolerant cultivars is an effective wayto minimize yield loss due to flooding. Information on candidate genes for flooding tolerance is useful for developing tolerant lines. Theobjective of this study was to identify potential candidate genes for flooding tolerance in soybean by integrating the results of a quantitativetrait locus analysis and RNA sequencing. A total of 19 genes showed good amplification in capillary electrophoresis and were further analyzedthrough a reverse transcription quantitative polymerase chain reaction (qRT-PCR); two of these genes showed differential expression amongtolerant and susceptible lines. The expression of Glyma.12g030900 and Glyma.10g050300 in leaf and root tissues, respectively, was higherin several tolerant lines than in the susceptible lines under flooding stress. The chlorophyll index of the tolerant lines was also consistentlyhigher than that of the susceptible lines over two years, supporting the qRT-PCR results. This study provides useful information on floodingtolerance in soybeans. KCI Citation Count: 0